FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM PERUSAHAAN TELEKOMUNIKASI - Sri Elviani; Ramadona Simbolon; Sri Puspa Dewi (Universitas Islam Islam Sumatera Utara, 2019)
The purpose of this study was to analyze the effect of Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER) and Earning per Share (EPS) towards the share price of telecommunications companies in Indonesia. The population of this study is a company engaged in telecommunications registered on the Indonesia Stock Exchange in 2012-2017. This study used a purposive sampling method which resulted in a total sample of 30 samples. The analysis technique of this study uses multiple linear regression to describe the relationship between one variable with other variables. The results of this study indicate that the ROE, and DER variables have a positive and significant effect on the share price of telecommunications companies, for the variables ROA, NPM, DAR and EPS do not have a positive and significant effect on the share price of telecommunications companies. On the other hand, the variables ROA, ROE, NPM, DAR, DER and EPS together have an influence on the share price of telecommunications companies. The adjusted R-Square value is 0.538, this means that 53.8% of the dependent variable stock price can be influenced by the variables ROA, ROE, NPM, DAR, DER and EPS.